Offender Reentry and Employment - Drury, Alan (2013)
This dissertation is an exploratory examination of offender re-entry and employment programming as contextualized by Bushway & Apel (2012) using the Serious and Violent Offender Re-entry Initiative (SVORI) Data. Propensity scores are used to examine both weighted and un-weighted logistic regression models. Logistic regression models indicate that inmate participation in employment programming during a term of incarceration increases employment rates for females at nine and fifteen months after their release but does not increase employment rates for males. In addition, participation in employment programming during a term of incarceration does not significantly reduce re-arrest rates among either gender. However, participation in community based employment programming significantly increases employment rates among females at three and nine months following their release and significantly increases male employment rates at three, nine, and fifteen months after their release. Participation in community based employment programming following a term of incarceration significantly reduced re-arrest rates among both genders for the time periods examined. Theoretical implications are explored